The influence of some indices of accountability for quality educational programmes in Oyo state, Nigeria (2009)
Accountability was traditionally used to refer to public service, in which stewardship of public funds must be accounted. Accountability as an educational concept, in recent years, has to do with advancing the effectiveness of school systems. If educators are to be accountable for students’ performance, the expected performance should be clearly stated and adequately measured. Accountability should also provide information on how money has been spent, especially on infrastructure/facilities, teachers salaries and what return has been made on investment in terms of students’academic achievement. In this regard, researchers (Obemeata 1995, and Yoloye 2003, 2004) emphasized the need for accountability to demonstrate returns of taxpayer’s money invested in education. For instance, Mark (2009), in a paper titled “Looking into Linking Teacher Pay to Student Performance” stated that President Obama “laid out his vision for education... including linking teacher pay to student performance”. For accountability to flourish there must be a positive link between accountability on the teachers ’ part and the salaries they are paid for their particular job which is teaching. Schrag added that teachers are answerable for what they do.